Ceftriaxone pharmacokinetic properties during continuous veno-veno haemofiltration using an in vitro adult, paediatric and neonatal model. (January 2014) - Harvey, B; Johnson, TN; Yeomanson, D; Mulla, H; Mayer, AP
During continuous venoveno haemofiltration (CVVH), extracorporeal drug clearance is dependant on blood flow, ultrafiltration rate, albumin binding, and the drug's molecular weight and volume of distribution. Drug doses are adjusted assuming reduced drug clearance by the renal system and CVVH. High volume haemofiltration, pre-dilution and different filter membranes can greatly alter drug clearance. Consequently, assessing the adequacy of cephalosporin dosing during CVVH is complex; under- or overdosing may occur. We studied the pharmacokinetic properties of ceftriaxone during CVVH in vitro. Renaflow filters were used to model 6, 20 and 50 kg patients. Each circuit and reservoir was prepared with a known volume of Hartmann's solution, human albumin solution 4.5% or blood. Pump speed and exchange rate were standardised for weight. Haemosol BO was used as the replacement fluid with 70% pre-dilution. Following paired sampling from the circuit and ultrafiltrate fluid, ceftriaxone was injected into the circuit. Paired samples were taken up to 720 minutes. Ceftraxione concentrations were determined using high performance liquid chromatography (HPLC). Maximum circuit concentrations (Cmax) at 2 minutes for albumin were 3.5, 2.65 and 4.85 mg/l, for blood were 4.5, 6.5 and 5.55 mg/l and for Hartmann's were 1.65, 2.95 and 3.65 mg/l for 6kg, 20kg and 50kg models. The sieving coefficients (Sc) from blood (ratio of mean concentrations in the ultrafiltrate/circuits samples) were 0.31 and 0.51 with T1/2 (the half life) 62 and 20 minutes in the 6kg and the 20kg circuits, respectively. The data suggest in an in vitro model of ceftriaxone is rapidly cleared during CVVH. Albumin circuits had the lowest Sc and longest terminal T1/2, reflecting protein binding of the drug and suggest ceftriaxone clearance may be more rapid in hypoalbuminaemic patients. The Cmax was lower in the Hartmann circuits, possibly reflecting precipitation of the drug with calcium in this solution.